Hypothetical Learning Trajectory Strategy in Ethno-Realistic Mathematics Education: An Exploration of Damar Kurung - Wiryanto; Habibie, Ramadhan Kurnia; Nurlaily, Vivi Astuti (Jurnal Elementaria Edukasia, 2024)
This study investigates the use of Damar Kurung Gresik, a traditional Indonesian art form, to enhance mathematics education for 4th-grade students through the Hypothetical Learning Trajectory strategy within Ethno-Realistic Mathematics Education. The aim is to integrate local cultural elements into the curriculum to foster better student engagement and understanding through contextual learning. Employing a Design Research methodology, the study was conducted with 32 elementary students. Data collection methods included classroom observations, interviews with teachers and students, and document analysis. The Hypothetical Learning Trajectory framework was applied to teach geometry, measurement, and pattern recognition, using Damar Kurung as a pedagogical tool to connect mathematical concepts with the art-making process. Findings indicate that the familiar context of Damar Kurung significantly increased student interest and motivation. Moreover, students exhibited improved comprehension and application of mathematical concepts, demonstrating considerable progress along the learning trajectory. Teachers reported that the structured approach provided by the Hypothetical Learning Trajectory facilitated more effective lesson planning and delivery, leading to enhanced learning outcomes. The study concludes that incorporating Damar Kurung into mathematics education through the Hypothetical Learning Trajectory strategy within the Ethno-Realistic Mathematics Education framework holds substantial promise for improving the quality of learning and mathematical understanding among 4th-grade students. This approach not only enriches the educational experience by making it more relevant to students' cultural backgrounds but also supports the development of critical thinking and problem-solving skills in mathematics.